PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, TERHADAP KINERJA KARYAWAN (STUDI KASUS KANTOR NOTARIS DENI SUBARNO, SH., M.KN) - Frassima Kusuma (Jurnal Pijar, 2024)
The success or failure of an organization in fulfilling its mission and functions is closely related to the actors or human resources in the organization. This research aims to measure how influential leadership and organizational culture are on employee performance at the office of Notary Deni Subarno, SH., M.KN. The research population was Notary Deni Subarno's employees, totaling 80 people. Data was obtained using a questionnaire with 46 respondents. Data processing uses SPSS 29.0.2.0 analysis tools with multiple liner analysis techniques which include validity tests, reliability tests, and classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, then hypothesis tests consisting of t tests and t tests. F. The results of research show that leadership does not have a significant influence on employee performance, while organizational culture has a significant influence on employee performance, so to be able to improve employee performance, Leaders must focus on their leadership and organizational culture.